Prohibiting alcohol sales during the coronavirus disease 2019 pandemic has positive effects on health services in South Africa - Hermann Reuter; Louis S. Jenkins; Marischka De Jong; Steve Reid; Michael Vonk (AOSIS, 2020)
As the coronavirus disease 2019 (Covid-19) pandemic evolves globally, we are realising its impact on communities from the disease itself and the measures being taken to limit infection spread. In South Africa (SA), 62 300 adults die annually from alcohol-attributable causes. Alcohol-related harm can be reduced by interventions, such as taxation, government monopolising retail sales, outlet density restriction, hours of sales and an advertising ban. To mitigate the impact of the Covid-19 pandemic, SA instituted a lockdown that also prohibited alcohol sales. This led to a sharp reduction in unnatural deaths in the country from 800-1000/week to around 400/week during the lockdown. We reviewed three 2-week periods at a large rural regional hospital: Before Covid-19 (February), during social distancing (March) and during lockdown with alcohol ban (April). A dramatic drop in patient numbers from 145 to 64 (55.8%) because of assault, from 207 to 83 (59.9%) because of accidents, from 463 to 188 (59.4%) because of other injuries and from 12 to 1 (91.6%) because of sexual assaults was observed during the first 2 weeks of lockdown. As healthcare professionals, we need to advocate for the ban to remain until the crisis is over to ensure that health services can concentrate on Covid-19 and other patients. We encourage other African states to follow suit and implement alcohol restrictions as a mechanism to free up health services. We see this as an encouragement to lobby for a new normal around alcohol sales after the pandemic. The restrictions should focus on all evidence-based modalities.